Mangroves Addition as Innovation for Sustainable Tourism - Hillary, Janne (Journal of Tourism Sustainability, 2023)
Grand Maerokoco is a tourist site in Semarang, located close to Marina beach. The presence of mangroves in Maerokoco, is expected to protect it from the coastal disaster, as well as to make it as a new attraction. This study assessed the benefits of mangroves addition in Grand Maerokoco according to visitor perception, economic valuation toward mangrove plantation in there, and its ability to reduce noises. Visitor perception could be known by conducting interviews. Economic valuation measurement employed was TCM (Travel Cost Method). Then for determining the ability to reduce noises, a noise measurement using sound level meter was conducted. Based on visitor perception, existence of mangroves in Grand Maerokoco can increase the attraction, increase the number of visitors, make the air cooler and cleaner, reduce the noise, and prevent the entry of coastal floods. The existing noise known at some point of crowds is still below the threshold standards of the EPA (Environmental Protection Agency), caused by mangroves in Maerokoco are high and dense. The potential consumer surplus value per individual per visit is Rp717,792.00. The value indicates the visitors get the benefits of environmental services greater than the cost incurred. For increasing the values, utilizing mangroves for education and agribusiness functions, along with maintenance should be done.